A Lamb waves-based wireless power transmission system for powering IoT sensor nodes. (1st October 2022) - Xu, Yunfei; Sun, Yongshun; Tang, Jian; Wei, Chao; Ding, Xiaoxi; Huang, Wenbin
Abstract: Sensor nodes (SNs) are widely deployed for condition monitoring within closed thin-walled structures. Conventional wired power supply using cables will affect the structural integrity, and wireless power supply based on inductive coupling will be shielded by metal structures, therefore, neither is desirable. Motivated by these issues, this article presents a Lamb waves wireless power transmission (WPT) technology based on piezoelectric wafer active sensors (PWASs). A PWAS with a diameter of 7 mm was used to excite A0 single-mode Lamb waves on a 1.6 mm aluminum plate at a frequency of 150 kHz for power transmission. Two optimization strategies for the Lamb waves-based WPT system were proposed and designed, including electrical impedance matching and beamforming with a linear PWAS array. The optimization effects of these two methods were analyzed experimentally. By combining these two approaches, the maximum received power is 1.537 mW, which is 384.25 times higher than that without the optimization method. The corresponding transmission efficiency is 0.217%, which is 43.4 times higher than that without the optimization method. A power management circuit was built with a maximum output power of 1.41 mW and a corresponding conversion efficiency of 77.5%. Finally, an internet-of-things (IoT) SN is designed, and a test proves that the proposed WPT system can power IoT SNs.